Synthesis and Characterization of New Schiff Bases Derived from N (1)-Substituted Isatin with Dithiooxamide and Their Co(II), Ni(II), Cu(II), Pd(II), and Pt(IV) Complexes - Ahlam J. Abdul-Ghani; Asmaa M. N. Khaleel (Bioinorganic Chemistry and Applications)
Three new Schiff bases of N-substituted isatin LI, LII, and LIII = Schiff base of N-acetylisatin, N-benzylisatin, and N-benzoylisatin, respectively, and their metal complexes C1a,b=[Co2(LI)2Cl3]Cl, C2=[Ni(LI)2Cl2]0.4BuOH, C3=[CuLICl(H2O)]Cl⋅0.5BuOH, C4=[Pd(LI)2Cl]Cl, C5=[Pt(L1)2Cl2]Cl2⋅1.8EtOH.H2O, C6a=[CoLIICl]Cl⋅0.4H2O⋅0.3DMSO, C6b=[CoLIICl]Cl⋅0.3H2O⋅0.1BuOH,C7=[NiLIICl2], C8=[CuLII]Cl2⋅H2O0𝑥000𝑎0, C9=[Pd(LII)2]Cl2, C10=[Pt(LII)2.5Cl]Cl3, C11a=[Co(LIII)]C12⋅H2O, C11b=[Co(LIII)]Cl2⋅0.2H2O, and C12=[Ni(LIII)2]Cl2, C13=[Ni(LIII)2]Cl2 were reported. The complexes were characterized by elemental analyses, metal and chloride content, spectroscopic methods, magnetic moments, conductivity measurements, and thermal studies. Some of these compounds were tested as antibacterial and antifungal agents against Staphylococcus aureus, Proteus vulgaris, Candida albicans, and Aspergillus niger.